Social policy and citizenship the changing landscape - Evers, Adalbert; Guillemard, Anne Marie (New York ; Oxford : Oxford University Press, 2013)
Taking nine European countries as case studies, the contributions to this volume analyze the ways that citizenship has changed in key areas such as social security, labor market policies and social services.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Oct. 30, 2012).
Keywords: Europe -- Social policy -- Case studies; Social service -- Europe -- Case studies; Manpower policy -- Europe -- Case studies